2004
DOI: 10.1038/sj.hdy.6800515
|View full text |Cite
|
Sign up to set email alerts
|

The role of tetraploids in the sexual–asexual cycle in dandelions (Taraxacum)

Abstract: Apomictic plants often produce pollen that can function in crosses with related sexuals. Moreover, facultative apomicts can produce some sexual offspring. In dandelions, Taraxacum, a sexual-asexual cycle between diploid sexuals and triploid apomicts, has been described, based on experimental crosses and population genetic studies. Little is known about the actual hybridization processes in nature. We therefore studied the sexual-asexual cycle in a mixed dandelion population in the Netherlands. In this populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 41 publications
2
50
0
Order By: Relevance
“…Detailed information about the information sources for the individual populations can be found in electronic supplementary material, table S1. The populations in Germany were shown earlier to consist mainly of triploids, while plants in the Swiss Alps are mostly diploid [29,35], allowing us to study the impact of M. melolontha on the evolution of secondary metabolites in both triploid apomictic and diploid obligate outcrossing plants. In both Germany and the Swiss Alps, we analysed three to four local herbivory, local control and regional control populations in spring 2013.…”
Section: Materials and Methods (A) Identification And Characterizationmentioning
confidence: 99%
“…Detailed information about the information sources for the individual populations can be found in electronic supplementary material, table S1. The populations in Germany were shown earlier to consist mainly of triploids, while plants in the Swiss Alps are mostly diploid [29,35], allowing us to study the impact of M. melolontha on the evolution of secondary metabolites in both triploid apomictic and diploid obligate outcrossing plants. In both Germany and the Swiss Alps, we analysed three to four local herbivory, local control and regional control populations in spring 2013.…”
Section: Materials and Methods (A) Identification And Characterizationmentioning
confidence: 99%
“…In contrast, the transition from triploidy to high ploidy levels has been reported in plants, e.g. in dandelions (Menken et al 1995;Verduijn et al 2004).…”
Section: Introductionmentioning
confidence: 90%
“…The second explanation is that balancing selection maintains clonal diversity, which includes diversity in pollen production. It is known that the pollen produced by asexuals, even though it is largely inviable, can occasionally pollinate sexual diploid dandelions, resulting in gene flow between the sexuals and asexuals (Verduijn et al, 2004). The occurrence of gene flow between sexuals and Number of seed heads and percentage of inviable seeds were log-transformed; the percentage of seeds that germinated was arcsinetransformed prior to analysis.…”
Section: Fitness Benefit Of Male Sterilitymentioning
confidence: 99%
“…To reach this balance, the effective rate of production of new clonal lineages through pollen produced by asexuals has to be equal to the same 38% per generation. In a study of a dandelion population containing both sexuals and asexuals, Verduijn et al (2004) found that less than 2% of the offspring produced by sexuals was polyploid. Even if newly produced clonal lineages have a fitness benefit compared to the existing lineages (eg due to purging of deleterious mutations or escape from specialised parasites), the rate of gene flow required to balance the fitness benefit of male sterility would have to be unrealistically high, especially when considering the finding that newly created clones had a much lower seed set than established clones (De Kovel and De Jong, 2000).…”
Section: Pg Meirmans Et Almentioning
confidence: 99%
See 1 more Smart Citation